Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw dalam Meningkatkan Hasil Belajar Siswa Mata Pelajaran Pendidikan Agama Islam di SMP Labschool UNESA 1 Surabaya: Pengabdian - Mohammad Shohib; Laila Badriyah; Eli Masnawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study was to evaluate how the puzzle type cooperative learning model significantly improves the learning outcomes of Islamic Religious Education of Grade VII at SMP Labschool Unesa 1 Surabaya. This study is a quantitative descriptive study using a sample of 97 students as its population. The sampling method used in this study was total sampling because the population was less than 100 people. The resulting regression equation is Y = 8.014 + 0.752 The puzzle cooperative learning model has a regression coefficient of 0.752 and is positive. This shows that if the puzzle cooperative learning model is increased by 1%, the learning outcomes will increase by 0.752. SMP Labschool Unesa 1 Surabaya noted a positive and significant influence of the Jigsaw type cooperative learning model on student learning outcomes in the Islamic Religious Education subject for Grade VII. The t-test results show a significant value of 0.000 <0.05 and a calculated value of 11.538> t table 1.985. This output provides a coefficient of determination (R2) value of 0.584. This means that the independent variable (puzzle style cooperative learning model) has an influence of 58.4% on the dependent variable (learning outcomes) and the remaining 41.6% is influenced by other variables not examined in this study.